2016
DOI: 10.1515/acgeo-2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Potential Field, Geoelectrical and Reflection Seismic Investigations for Massive Sulphide Exploration in the Skellefte Mining District, Northern Sweden

Abstract: Multi-scale geophysical studies were conducted in the central Skellefte district (CSD) in order to delineate the geometry of the upper crust (down to maximum ~ 4.5 km depth) for prospecting volcanic massive sulphide (VMS) mineralization. These geophysical investigations include potential field, resistivity/induced polarization (IP), reflection seismic and magnetotelluric (MT) data which were collected between 2009 and 2010. The interpretations were divided in two scales: (i) shallow (~ 1.5 km) and (ii) deep (~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The International Geomagnetic Reference Field (IGRF) correction was applied on the magnetic data with a total field intensity of 52,824, 76.7° inclination and declination of 8.5°. However, the regional field trend which has been defined and separated for magnetic and gravity data using the second polynomial degree (Tavakoli et al ., 2012a, 2012b, 2016a) for the magnetic data is somewhat lower than the IGRF value, that is, 51875 nT.…”
Section: Modelling Scheme and Data Processingmentioning
confidence: 70%
“…The International Geomagnetic Reference Field (IGRF) correction was applied on the magnetic data with a total field intensity of 52,824, 76.7° inclination and declination of 8.5°. However, the regional field trend which has been defined and separated for magnetic and gravity data using the second polynomial degree (Tavakoli et al ., 2012a, 2012b, 2016a) for the magnetic data is somewhat lower than the IGRF value, that is, 51875 nT.…”
Section: Modelling Scheme and Data Processingmentioning
confidence: 70%
“…IP and ER methods are among the most applicable geophysical methods used in subsurface studies notably for selection of the best drilling points for exploration purposes (Bishop and Emerson 1999;Wynn and Grosz 2000;Ferdows and Ramazi 2015b;Hope and Andersson 2016). Some examples of their increased usage include copper exploration using 3D IP modelling in NSW, Australia (Whaite et al 2001), using combination of ER and IP in polymetal deposit in China (Yang, Liu and Wang 2008), gold exploration at the eastern desert of Egypt by IP measurement (Taha et al 2018), combination of ER, IP and microgravity to detect buried caves in Spain (Martínez-Moreno et al 2013), copper exploration using IP and ER in Iran (Ramazi and Jalali 2014), gold-silver deposit exploration by IP method in Russia (Gurin et al 2015), detection of the uranium mineralization zone in India (Biswas and Sharma 2016), integration of geophysical methods including IP and ER methods for massive sulphide exploration in Sweden (Tavakoli et al 2016), bitumen mineralization exploration in the west of Iran (Mashhadi, Mostafaei and Ramazi 2017), gold deposit exploration by 3D-induced polarization modelling in Indonesia (Halim et al 2017), 3D tomography of induced polarization and its application in polymetallic mine (Jun-Lu et al 2017), copper mineral exploration using 3D model of IP and resistivity in Brazil (Morriera et al 2018), investigation of a rock glacier by 3D tomography of IP and ER in France (Duvillard et al 2018) and urban area investigation by 3D IP and ER in Stockholm (Pazzi et al 2018;Rossi et al 2017Rossi et al , 2018.…”
Section: Figurementioning
confidence: 99%
“…), detection of the uranium mineralization zone in India (Biswas and Sharma ), integration of geophysical methods including IP and ER methods for massive sulphide exploration in Sweden (Tavakoli et al . ), bitumen mineralization exploration in the west of Iran (Mashhadi, Mostafaei and Ramazi ), gold deposit exploration by 3D‐induced polarization modelling in Indonesia (Halim et al . ), 3D tomography of induced polarization and its application in polymetallic mine (Jun‐Lu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The correlation is not always very good, in some cases there is a shift in position and in others there are differences of shape or size (García Juanatey, 2012, Paper IV). Later on, Tavakoli et al (2016b) showed that it was possible to resolve these offsets by re-modelling the potential field data.…”
Section: Other Geophysical Datamentioning
confidence: 99%